Implementasi Kegiatan Projek Penguatan Profil Pelajar Pancasila (P5) dalam Kurikulum Merdeka di Sekolah Dasar - Christiananda, FR.; Purwaningrum, Nova Sugiana; Rofisian, Nela (CV. ITTC INDONESIA, 2023)
Learning activities in elementary schools that have implemented the Independent Curriculum have problems regarding the implementation of P5 activities. One of them is that the teacher still does not understand the concepts used in P5 activities. Teachers only emphasize the results of projects made by students without paying attention to the project creation process. So students cannot develop their creativity according to their interests and talents. The aim of this research is to find out how to implement P5 activities at the elementary school level with differentiated learning. The method we use in this research is qualitative with a library research approach using literature study. The objects of this research are students and educators at elementary school level who have used the Independent Curriculum. The research results show that P5 learning must use differentiated learning with 8 stages and choose several scheduling options.